2012
DOI: 10.1021/ac3019334
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Epifluorescence and Time-of-Flight Secondary Ion Mass Spectrometry Chemical Imaging Comparisons of Single DNA Microarray Spots

Abstract: DNA microarray assay performance is commonly compromised by spot-spot probe and signal variations as well as heterogeneity within printed microspots. Accurate metrics for captured DNA target signal rely upon uniform spot distribution of both probe and target DNA to yield reliable hybridized signal. While often presumed, this is neither easily achieved nor often proven experimentally. High resolution imaging techniques were used to determine spot heterogeneity in identical DNA array microspots comprising varied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 77 publications
0
44
0
1
Order By: Relevance
“…55 Printed dried probe spots often exhibit increased DNA density at spot centers compared to peripheries. This probe heterogeneity has implications for target uptake and resulting spot duplex heterogeneity as a consequence due to local differences in interfacial steric and coulombic properties that affect target-probe pairing efficiencies and kinetics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…55 Printed dried probe spots often exhibit increased DNA density at spot centers compared to peripheries. This probe heterogeneity has implications for target uptake and resulting spot duplex heterogeneity as a consequence due to local differences in interfacial steric and coulombic properties that affect target-probe pairing efficiencies and kinetics.…”
Section: Resultsmentioning
confidence: 99%
“…Target hybridization therefore occurs from spot edges radially inwards as indicated by increasing Cy5 emission spot intensity profiles (Figure 3). Both non-uniform radial probe density from spot drying 55 and target radial transport issues 15 produce non-homogeneous target hybridization with time. Target mass transport depends on array format (static vs. flow), target concentration, and its diffusion coefficient.…”
Section: Resultsmentioning
confidence: 99%
“…Routine conventional fluorescence scanner images provide information for integrated spot pixel intensity, shape and morphology, but lack important details for incorporating intra-spot ssDNA immobilized heterogeneity and intra-spot structural issues known to affect both target capture signals and duplex hybridization kinetics critical to this assay’s answer development and diagnostic reliability. [34] Additionally, signal quantitation is affected by numerous, known surface issues and background noise sources that confound reliable, quantitative correlations of spot-to-spot fluorescent assay signals and experiment-to-experiment comparisons. [17, 79] Significantly, integration of spot fluorescent intensity to report assay signal with commonly used fluorescence scanners demonstrates that the typical fluorescence scanner cannot discern microspot optical heterogeneity and fluorescence intensity variations within single printed spots to yield a reliable metric.…”
Section: Microarray Assay Signal Detectionmentioning
confidence: 99%
“…Inaccuracy in this fluorescent metric is attributed to fluorescent dye-dye and dye-surface interactions, leading to quenching of surface fluorescence signal. [34]…”
Section: Microarray Assay Signal Detectionmentioning
confidence: 99%
“…Next to biological and biochemical sources, bias originates from photochemical processes and depends on the choice of labeling agent as well as the selected imaging procedure and environment. In earlier works, it was shown that the ubiquitous application of cyanine dye labeling causes significant bias due to the dyes’ disparate susceptibility to photobleaching and possible FRET interaction [19,20,26,28,29]. …”
Section: Discussionmentioning
confidence: 99%